PERILAKU SEKSUAL REMAJA AKIBAT PAPARAN MEDIA PORNOGRAFI - Intan Tri Masroah; Elviera Gamelia; Bambang Hariyadi (Kesmas Indonesia, 2015)
The exposure of pornography media allegedly may affect the adolescents sexual behavior. The aim of this research was to describe adolescents knowledge, attitude, and sexual activities as the effects of pornography media exposure. The research design used qualitative descriptive method. There were six key informants and five supporting informants. Technique of determining the research subject was by snowball sampling. The result of the research showed that the types of pornography media used by adolescents were movies, videos, pictures, magazines, and porn sites. Exposure frequencies were once to three times a week. The supporting factors were boredom, dizziness, stress, amusement need, just for fun, and influence from peers. The knowledge obtained from pornography media were the types of pornography media, sexual intercourse processes, female’s physical appearance, way to seduce and stimulate female as well as the terms related to sexuality. Adolescents stated that they agreed in sexual activities as long as still in acceptable limit. The forms of sexual activities were masturbation, holding hands, embracing, hugging, kissing and petting.It is suggested to improve in providing information and education about pornography media and sexual behavior and adolescents can take steps to prevent the impact of pornography media exposure and sexual behavior.